2019
DOI: 10.22437/ifstj.v2i2.9442
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Heating Schedule on Physico-Chemical Properties of Instant Coffee of Liberika Tungkal Jambi

Abstract: Abstract— The making of instant brewed coffee using co-crystallization method is strongly influenced by the heating schedule (HS) applied. Five levels of HS (HS1, HS2, HS3, HS4 and HS5) were studied on the physico-chemical properties of instant coffee of Liberika Tungkal Jambi. The treatment was applied in a completely randomized design with 4 replications. The coffee was extracted using a special coffee extractor in a ratio of hot water/coffee powder of 15/1. Parameters observed were moisture content, ash con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
3
1
Order By: Relevance
“…2983 of 2014 which states that the maximum water content is 5%. The values obtained in this research were observed to be higher than the 1.57 -1.61% reported by [21] for instant coffee from Tungkal Jambi and the 2.34% by [39] for cold-brewed instant coffee. Meanwhile, the values are in the same range as 4.4.% found by [15] for instant coffee produced from micro-size coffee combined with Bacillus coagulans.…”
Section: Water Contentcontrasting
confidence: 79%
“…2983 of 2014 which states that the maximum water content is 5%. The values obtained in this research were observed to be higher than the 1.57 -1.61% reported by [21] for instant coffee from Tungkal Jambi and the 2.34% by [39] for cold-brewed instant coffee. Meanwhile, the values are in the same range as 4.4.% found by [15] for instant coffee produced from micro-size coffee combined with Bacillus coagulans.…”
Section: Water Contentcontrasting
confidence: 79%
“…The solubility percentage of instant gambir coffee produced was higher than the solubility level of 93.79% for instant coffee made from robusta beans processed using a vacuum dryer, as reported by Matanari [16]. However, the value was lower than Tungkal Jambi Liberika instant coffee, which had a content of 97.95-98.20% [12].…”
Section: Resultsmentioning
confidence: 55%
“…The water content of instant gambir coffee produced in this research was higher than the Indonesian National Standard (SNI) No 2983 of 2014, set at 5%. The value was also greater than [4] at 3.84-4.81%, instant coffee from Tungkal Jambi, which has a content of 1.57-1.61% [12], and cold brewed instant coffee at 2.43% [13].…”
Section: Resultsmentioning
confidence: 76%
“…Maltodextrin has a DE value of 3-20, while dextrin is 3-5 (Wulansari et al, 2012). Mursalin et al (2019) reported that the solubility of instant Liberica coffee made by crystallizing granulated sugar (35%) was 97.95%.…”
Section: Results and Discussion Rendementmentioning
confidence: 99%